2015
DOI: 10.1002/phar.1566
|View full text |Cite
|
Sign up to set email alerts
|

Autoinduction of Voriconazole Metabolism in a Child with Invasive Pulmonary Aspergillosis

Abstract: Inter- and intra-patient variability in voriconazole pharmacokinetics has been described in children as the result of age-specific differences in hepatic metabolism, saturable nonlinear pharmacokinetics, CYP450 2C19 polymorphisms, decreased bioavailability compared with adults, and drug-drug interactions. We introduce dose-dependent autoinduction of metabolism as another cause for altered voriconazole pharmacokinetics in children and summarize previously published literature on this phenomenon. A 10-year-old g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
(77 reference statements)
0
7
0
1
Order By: Relevance
“…Although expression of FMO3 is similar in children and adults, it seems to contribute to higher metabolic clearance of voriconazole in children versus adults . In addition, autoinduction has been reported, which may further explain the difficulty in achieving and maintaining voriconazole serum trough concentrations in the desired range …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although expression of FMO3 is similar in children and adults, it seems to contribute to higher metabolic clearance of voriconazole in children versus adults . In addition, autoinduction has been reported, which may further explain the difficulty in achieving and maintaining voriconazole serum trough concentrations in the desired range …”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, autoinduction has been reported, which may further explain the difficulty in achieving and maintaining voriconazole serum trough concentrations in the desired range. 24 Additional strategies have been proposed to inform voriconazole dosing decisions before obtaining the first TDM result. Bayesian modeling-based tools are in development to use existing pharmacokinetic data to rapidly individualize voriconazole therapy in children.…”
Section: Discussionmentioning
confidence: 99%
“…Her initial trough level was therapeutic at 1.4 mg/mL on voriconazole 11 mg/kg/dose PO every 12 hours but required dose titration up to 9.3 mg/kg/dose PO every 8 hours to keep the trough level above 1 mg/mL. 24 More recently, Ferguson et al reported a case of autoinduction with voriconazole in a 36-year-old female being treated for CNS aspergillosis after immunosuppression treatment of suspected atypical hemolytic uremic syndrome/thrombotic thrombocytopenic purpura. She was started on voriconazole IV 6 mg/kg (500 mg) every 12 hours  2 doses followed by 4 mg/kg (320 mg) every 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole inhibits metabolism of the immunosupressant tacrolimus [24] [25]. Whether impaired voriconazole clearance and/or altered metabolism leads to periosteal changes, needs further study [28]. In 2015, Naito et al .…”
Section: Discussionmentioning
confidence: 99%